Application of citric acid and mild heat shock to minimally processed sliced radish: Color evaluation - Goyeneche, Rosario (2014)
The aim of this research was to study the effects of two hurdle technologies, citric acid application (CA) at 0.3%, 0.6% and 0.9% and thermal treatments (IT) for 1, 2 and 3 min at 50 °C, on the color of radish slices over 10 d of refrigerated storage. Contribution of the hurdles and their interactions were evaluated by examining the treatment effects on the following parameters: chromatic coordinates (L*, a* and b*) and the indices: chroma (ΔC*), total color difference (ΔE) and Color Index (CI*). The chromatic parameters for fresh radish (control samples) were L0 = 69.43 ± 0.62, a0 = −0.46 ± 0.05 and b0 = 5.37 ± 0.37, while the calculated color indices were chroma = 5.39 ± 0.36, ΔE = 0 and CI* = −1.19 ± 0.17. Regarding control samples, the b* values showed an increasing trend during storage, which was associated with browning of the slices. Both ΔE and ΔC* values presented similar trends as reported for b*. Based on statistical analysis of the parameters and indices tested, the single hurdle application of low citric acid concentration (0.3%) or intermediate immersion time (2 min) at 50 °C minimized the radish slices color changes during storage. However, better results were obtained when two hurdles in series were applied. According to analysis, the treatment T7 (1 min IT, 0.3% CA) was selected as the best treatment to improve the retention of typical natural color of the minimally processed sliced radishes.